PENGARUH KOMPETENSI DAN KETERLIBATAN KERJA TERHADAP PERILAKU KERJA INOVATIF DIMEDIASI OLEH KEPUASAN KERJA PADA ASN DI LINGKUNGAN PEMERINTAH KOTA PAYAKUMBUH - Erwan; Yulihasri (Journal Publicuho, 2024)
This study aims to examine the effect of competence and work involvement on innovative work behaviour mediated by job satisfaction in ASN in the Payakumbuh City government. A quantitative approach with hypothesis-testing techniques was used in this study. There were 160 samples with purposive sampling techniques, namely JPT/Echelon II officials, administrator officials (Echelon IIIA and IIIB), young/middle expert functional officials, and innovation management officials of the Payakumbuh City regional apparatus. Data were collected by distributing questionnaires online and processed using SmartPLS 3.0 software. The data analysis method uses structural equation modelling with partial least squares (SEM-PLS). The results showed that competence has a positive and significant effect on job satisfaction and innovative work behaviour. Job involvement has a positive and significant effect on job satisfaction but is not significant for innovative work behaviour. Job satisfaction has a positive and significant effect on innovative work behaviour. Job satisfaction is able to mediate the relationship between work involvement and innovative work behaviour but is unable to mediate the relationship between competence and innovative work behaviour. The implications of the research emphasize the importance of providing comfort to ASN while working so that they can be encouraged to work innovatively.